Empowering Educators Practical Instructional Workshop at CML, UMPSA enhances Instructional Approaches for the 21st Century - Hafizoah, Kassim; Wan Jumani, Fauzi; Amy Zulaikha, Mohd Ali (UMPSA, 2024)
PEKAN, 19 August 2024 – In today's rapidly evolving educational landscape, adopting new instructional approaches are essential for language instructors to effectively engage and support their students.